Development of optical choppers for time‐resolved measurements at soft X‐ray synchrotron radiation beamlines. (24th March 2017) - Osawa, Hitoshi; Ohkochi, Takuo; Fujisawa, Masami; Kimura, Shigeru; Kinoshita, Toyohiko
Abstract : Two types of optical choppers for time‐resolved measurements in soft X‐ray beamlines of synchrotron radiation facilities were developed, which are utilized under ultra‐high‐vacuum conditions. Abstract : Two types of optical choppers for time‐resolved measurements at synchrotron radiation soft X‐ray beamlines have been developed. One type uses an air‐spindle‐type rotation mechanism with a two‐stage differential pumping system to maintain the ultra‐high vacuum of the X‐ray beamline, and the other uses a magnetic bearing. Both can be installed at the soft X‐ray beamlines at SPring‐8, greatly improving the accessibility of pump‐and‐probe spectroscopy. The combination of X‐ray chopper and pump‐and‐probe photoemission electron microscope at SPring‐8 provides drastic improvements in signal‐to‐noise ratio and resolution compared with techniques using high‐voltage gating of channel plate detectors. The choppers have the capability to be used not only at synchrotron radiation facilities but also at other types of soft X‐ray and VUV beamlines.